Organophosphorus pesticide residues in vegetables from farms, markets, and a supermarket around Kwan Phayao Lake of Northern Thailand - Ratana Sapbamrer (2018)
This study investigated organophosphorus (OP) residues in vegetables from 27 farms, 106 markets, and 1 supermarket around Kwan Phayao Lake, Northern Thailand, between August and September 2013. Types of vegetables sampled were all vegetables cultivated or sold around the study site. The most common OP pesticides detected in farm samples were chlorpyrifos (50 %), malathion (31.8 %), monocrotophos (31.8 %), diazinon (13.6 %), omethoate (13.6 %), and dicrotophos (9.1 %). The most common OP pesticides detected in market samples were chlorpyrifos (33.9 %), diazinon (18.6 %), parathion-methyl (3.4 %), profenofos (3.4 %), primiphos-ethyl (3.4 %), and fenitrothion (1.7 %). The OP pesticides detected in supermarket samples were chlorpyrifos (33.3 %), and diazinon (66.7 %). Among the compounds detected, chlorpyrifos was detected in most of the vegetable samples from all sources. The highest chlorpyrifos level in farm samples were found in lemon balm (2.423 mg/kg) followed by Vietnamese coriander (0.835 mg/kg), and cowpea (0.027 mg/kg). The highest level in markets samples were found in garlic (7.785 mg/kg) followed by Chinese cabbage (2.864 mg/kg) and Vietnamese coriander (1.308 mg/kg). Residues from supermarket samples were found only in parsley (0.027 mg/kg). The findings showed that 16 samples (59.3 %) from farms and 14 samples (13.2 %) from markets contained OP residues at or above the maximum residue limits established by the European Union. It is concluded that awareness, safety education, and strict regulation of pesticide use are necessary. © Springer Science+Business Media New York 2014.